2022
DOI: 10.1038/s41368-022-00174-4
|View full text |Cite
|
Sign up to set email alerts
|

FAM64A promotes HNSCC tumorigenesis by mediating transcriptional autoregulation of FOXM1

Abstract: Head and neck squamous cell carcinoma (HNSCC) still lacks effective targeted treatment. Therefore, exploring novel and robust molecular targets is critical for improving the clinical outcome of HNSCC. Here, we reported that the expression levels of family with sequence similarity 64, member A (FAM64A) were significantly higher in HNSCC tissues and cell lines. In addition, FAM64A overexpression was found to be strongly associated with an unfavorable prognosis of HNSCC. Both in vitro and in vivo evidence showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…FAM64A not only augmented the transcriptional activity of FOXM1 but also regulated FOXM1 expression through an autoregulatory loop, thereby promoting the tumorigenesis of HNSCC. Previously, FAM64A expression was found to upregulate in, osteosarcoma (Jiang, Zhou, et al, 2020), breast cancer (Yao et al, 2019), glioma (Wang et al, 2021), lung cancer (Jiang et al, 2021), cholangiocarcinoma (Jiang, Li, et al, 2020), and HNSCC (Zhao et al, 2022), in line with our data. FAM64A mRNA expression was found to negatively associate with the purity and loss infiltration of immune cells in GC and no immunopositivity of FAM64A was observed in the infiltrative immune cells, which accounted for the consistency between our morphological and molecular findings.…”
Section: Effect Of Fam64a Expression On Chemoresistance and Lipid Dro...supporting
confidence: 91%
See 2 more Smart Citations
“…FAM64A not only augmented the transcriptional activity of FOXM1 but also regulated FOXM1 expression through an autoregulatory loop, thereby promoting the tumorigenesis of HNSCC. Previously, FAM64A expression was found to upregulate in, osteosarcoma (Jiang, Zhou, et al, 2020), breast cancer (Yao et al, 2019), glioma (Wang et al, 2021), lung cancer (Jiang et al, 2021), cholangiocarcinoma (Jiang, Li, et al, 2020), and HNSCC (Zhao et al, 2022), in line with our data. FAM64A mRNA expression was found to negatively associate with the purity and loss infiltration of immune cells in GC and no immunopositivity of FAM64A was observed in the infiltrative immune cells, which accounted for the consistency between our morphological and molecular findings.…”
Section: Effect Of Fam64a Expression On Chemoresistance and Lipid Dro...supporting
confidence: 91%
“…These effects were achieved by obstructing the negative feedback loop of NF‐κB/IκBα and facilitating the nuclear accumulation and transcriptional activity of NF‐κB. Zhao et al (2022) reported that FAM64A levels progressively increased from normal to dysplastic to cancerous tissues in a carcinogenic mouse model induced by 4‐nitroquinoline‐1‐oxide. Physical interaction between FAM64A and FOXM1 (forkhead box protein M1) was uncovered in head and neck squamous cell carcinoma (HNSCC) cells as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because FOXM1 could be transcriptionally upregulated by itself ( 34 ), we further analyzed the correlation between RNF112 and FOXM1 in The Cancer Gene Atlas (TCGA) database. Notably, a marked inverse association between RNF112 and FOXM1 was noticed in gastric cancer compared with the other 32 tumor settings, indicating the RNF112/FOXM1 axis is relatively more important in gastric cancer ( Supplemental Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Squamous cell carcinoma of the head and neck (HNSCC) developed from the epithelium of the pharynx and oral mucosa is the sixth most common malignancy worldwide ( 1 ). The most closely associated causative factors for HNSCC include aging, exposure to environmental pollutants, family history, Epstein-Barr virus (EBV)/human papillomavirus (HPV) infection, and poor lifestyle habits, such as smoking and alcohol abuse ( 2 ). HPV (–) is the most common type of HNSCC and results in a worse prognostic outcome than (+) HNSCC ( 3 ).…”
Section: Introductionmentioning
confidence: 99%